Determination of total antioxidant capacity in marmalade and marshmallow - Gubsky, Sergey; Artamonova, Maiia; Shmatchenko Nataliа; Piliugina, Inna; Aksenova, Elena (Eastern-European Journal of Enterprise Technologies, 2016)
Creation of functional foods with various plant additives as a preventive means of population antioxidant protection programs is an important task, the solution of which is impossible without a preliminary assessment of antioxidant properties of food components – plant material. For this purpose, the antioxidant capacity of plant additives of apples, quince, grapes, pumpkins, carrots, rose hips, sea buckthorn, Sudanese rose, black chokeberry, obtained by cryogenic technologies and products with them – fruit jelly and marshmallow was investigated by galvanostatic coulometry. It was found that the TAC of cryopastes increases in the row: pumpkins<carrots<quince<apples<grapes from 25 to 550 C/100 g. The TAC of cryopowders increases in the row: grapes<black chokeberry<Sudanese rose<sea buckthorn<rose hips from 663 to 4400 C/100 g. The values correlate with the content of the main classes of antioxidants in these cryoadditives. It was determined that marmalade with the addition of carrot and pumpkin cryopastes has the lowest bromine TAC. Additional introduction of cryopowders in marmalade samples with cryopastes in an amount 1.5 % increases the TAC of marmalade by 3.5–10 times. It is shown that the use of wateralcohol extracts as additives with the addition of 1 % citric acid provides the samples of marshmallow with more pronounced antioxidant properties. The calculations, based on the additive scheme show that the functional properties of the products are due to the antioxidant properties of the additives.